THE ARTIFICIAL NOSE-BASED PMMA-rGO COMPOSITE COATED QCM SENSOR TO SNIFF COFFEE AROMA AT DIFFERENT ROASTING DEGREE - Nalle, Ferry Chrismiadi; Sabarudin, Akhmad; Sakti, Setyawan Purnomo (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2024)
The quality of a product, including coffee, can be determined by its aroma, which is influenced by various chemical compounds. Human olfactory-based assesment and other technologies have been developed to assess coffee aroma; however, these methods are often costly and require highly trained professionals. Gravimetric-based sensors, such as quartz crystal microbalance (QCM) sensors, offer high sensitivity, ease of use, and the capacity to modify their effective surface with nanomaterials. In this research, an artificial nose-based QCM sensor has been modified using a material-sensitive polymethyl methacrylate-reduced graphene oxide (PMMA-rGO) composite.The composite materials were synthesised using an in-situ polymerisation method in the presence of dual solvent. IR characterisation revealed PMMA and PMMA-rGO spectra to be highly similar, suggesting successful trapping of rGO within the PMMA matrix via physical interaction. Increasing the content of rGO resulted in a slight increase in the surface roughness of the QCM sensor.The composite-based QCM sensor demonstrated the capacity to detect coffee aroma at three distinct roasting temperatures (220℃, 225℃, and 230 ℃). The highest response was observed in sample PR1, with a value of -35.2 Hz (220℃), -44.3 Hz (225℃), and -83 Hz (230℃) for the variation in the amount of rGO in the polymer matrix. The presence of rGO with their surface area properties enhanced the QCM sensor to detect coffee aroma.